Optimal configuration and resolution for the first convection‐permitting ensemble of climate projections over the United Kingdom. (17th December 2019) - Fosser, Giorgia; Kendon, Elizabeth; Chan, Steven; Lock, Adrian; Roberts, Nigel; Bush, Mike
Abstract: Convection‐permitting models (CPMs) provide a better representation of sub‐daily precipitation statistics and convective processes on both climate and weather forecasting timescales. This study aims to establish what horizontal resolution and physical process settings are suitable for the first ensemble of convection‐permitting climate projections for the United Kingdom. For this purpose, 12‐year‐long simulations were run using three different convection‐permitting resolutions (grid spacing of 4 km, 2.2 km and 1.5 km) each with several configurations. The focus is on the ability to represent sub‐daily precipitation due to its potential for high impacts on society through flooding. The analysis shows that the use of a finer grid spacing within the convection‐permitting regime improves the representation of sub‐daily precipitation but the added value decreases as the grid becomes increasingly finer, while the computational costs substantially increase. Changes in the representation of physical processes can have as much impact as the grid spacing and can lead to similar differences in the diurnal cycle as between convection‐parametrized models and CPMs. Although the 4km model shows some key deficiencies that make it unreliable for climate projection, the 2.2km model performs as well as the 1.5km model for most of the metrics examined with considerable benefits in terms of computer cost. The optimal configuration and resolution identified here is being used for an ensemble of simulations run within the UK Climate Projections 2018 (UKCP18) project, which allows, for the first time, an estimate of uncertainty in future changes at convection‐permitting scale and providing more reliable climate change projections at local and hourly scales. Abstract : Convection‐permitting models provide a better representation of sub‐daily precipitation statistics and convective processes compared with coarser resolution models on both climate and weather forecasting timescales. Using 12‐year‐long simulations, this study investigates what convection‐permitting resolution and physical process settings are suitable for the first ensemble of convection‐permitting climate projections for the United Kingdom. The focus is on the ability to represent sub‐daily precipitation due to its potential for high impacts on society through flooding.